PERBEDAAN TINGKAT KECEMASAN PADA PASIEN CONGESTIVE HEART FAILURE KELAS FUNGSIONAL 1 DAN 2 DI POLIKLINIK JANTUNG RSUD AL-IHSAN TAHUN 2020 - Istianah Istianah; Muhammad Deri Ramadhan (Jurnal Kesehatan Rajawali, 2020)
Background: Congestive Heart Failure (CHF) is not only a physical problem that affects the sufferer, but CHF can also affect the sufferer psychologically, one of which is anxiety. Objective: To differentiate the level of anxiety inpatients in Congestive Heart Failure functional class 1 and 2 at Al-Ihsan Hospital. Methods: The study design used an observational study to differentiate the level of anxiety in CHF patients in functional class 1 and 2. The design used quantitative analytic with aapproach cross sectional in this study, with a sample of 102 CHF patients in functional classes 1 and 2. The analytical test used was Chi. - Square. Results: Researchers obtained patient demographic data in the form of age, gender, and occupation. The results showed that CHF patients in functional class 1 showed less anxiety, compared to functional class 2, with p = 0.001, these results showed a difference in the level of anxiety. Conclusion: from this study there is a difference in anxiety in patients with Congestive Heart Failure functional class 1 and 2.